Examination of β-lactoglobulin-ferulic acid complexation at elevated temperature using biochemical spectroscopy, proteomics and molecular dynamics. (January 2023) - Abdollahi, Kourosh; Condict, Lloyd; Hung, Andrew; Kasapis, Stefan
Abstract: The molecular nature of interactions between ferulic acid and β-lactoglobulin was investigated following exposure of solutions to high temperature (121 °C) at near neutral pH (7.3) using biochemical spectroscopy, proteomics and molecular dynamics. Circular dichroism (CD) and infrared spectroscopy (FTIR) argue for alterations in the secondary structure of the heated protein molecule in the presence of the ligand. In addition, UV–vis recorded a considerable increase in the absorption of the β-lactoglobulin-ferulic acid preparation following heat treatment, an outcome which indicates the formation of a covalent interaction between the two components in the mixture. Molecular docking studies in combination with molecular dynamics simulations predicted the covalent interaction between lysine 100 and the aromatic ring of the phenolic acid along with a range of non-covalent bonds to form a new adduct. Protein hydrolysis experiments combined with MALDI-TOF MS analysis demonstrated the chemical nature of interaction between ferulic acid and ε amino group of the amino acid. It is hoped that the work will provide a broader understanding of the molecular interactions between phenolic acids and dairy proteins following thermal treatment at elevated temperature. Graphical abstract: (a) 3D image of the best binding locations of ferulic acid docked onto each monomer of the β-lactoglobulin dimer (b) close up image of the interacting amino acids and distances (Å) from ferulic acid and (c) 2D representation of the binding sites between ferulic acid and interacting amino acids at pH 7.3 and 121 °C. Image 1 Highlights: Interactions in β-lactoglobulin-ferulic acid mixtures were studied following UHT treatment. The conformational structure of the protein in the binary mixture is less ordered. A covalent bond is formed between the aromatic ring of ferulic acid and εN of lysine 100. The protein-ligand adduct is further stabilized by hydrogen bonding and π-alkyl stacking.